COMPARATIVE ANALYSIS OF VENOM PROTEIN PROFILE BY SDS-PAGE OF THREE COMMON SPECIES OF SCORPIONS (SCORPIONES: BUTHIDAE) IN BALOCHISTAN, PAKISTAN - N. Akbar; 2; A. Sajjad; S. Rizwan; H. M. Tahir; Z. Mehmood; K. Mehmood; S. Munir; S. A. Ali; Rakhshanda; A. Mushtaq (Journal of Animal and Plant Sciences, 2022)
This is the first reported study conducted for partial characterization of venom from three scorpion species (Odontobuthus odonturus, Androctonus finitimus and Androctonus bicolor), collected from different regions of Balochistan, Pakistan. The venom was extracted and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and results revealed the presence of different peptides ranged from 6 kDa to 121 kDa. Peptide bands of 68 kDa, 13 kDa and 6 kDa were found common in all the three venom samples, while peptide bands of 121 kDa, 44 kDa and 23 kDa were shared between Androctonus finitimus and Androctonus bicolor, similarly 29 kDa of band was common in Androctonus finitimus and Odontobuthus odonturus. Furthermore, each scorpion species had a minimum of one unique peptide band. The similar electrophoretic characteristics of some peptide components suggested inter-genus and inter-species relationships among different species. Conversely each sample of examined species also represents a distinctive profile that differentiates one species from another thus providing a simple tool for taxonomical studies.
Keywords: scorpions; venom; venom extraction; protein; SDS-PAGE